IEEE Winter Conference on Applications of Computer Vision 2014
DOI: 10.1109/wacv.2014.6836020
|View full text |Cite
|
Sign up to set email alerts
|

Video alignment to a common reference

Abstract: Video Alignment to a Common ReferenceHandheld videos often include unintentional motion (jitter) and intentional motion (pan and/or zoom). Human viewers prefer to see jitter removed, creating a smoothly moving camera. For video analysis, in contrast, aligning to a fixed stable background is sometimes preferable. This paper presents an algorithm that removes both forms of motion using a novel and efficient way of tracking background points while ignoring moving foreground points.The approach is related to image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Motion compensation can be accomplished for an entire video by aligning each frame in this way to the initial reference frame by cascading the homography transformations as proposed by Dutta et al [ 44 ] . We found, however, that this approach aggregated skew and perspective errors across frames because the points on which computation of the homography matrix was based were not consistent within each region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Motion compensation can be accomplished for an entire video by aligning each frame in this way to the initial reference frame by cascading the homography transformations as proposed by Dutta et al [ 44 ] . We found, however, that this approach aggregated skew and perspective errors across frames because the points on which computation of the homography matrix was based were not consistent within each region.…”
Section: Methodsmentioning
confidence: 99%
“…Dutta et al [ 44 ] identified breaks in a video sequence when the video starts panning or scale changes become substantial. Information from prior frames is not considered after a break and a new reference frame is introduced.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations